HUBUNGAN STATUS SOSIO DEMOGRAFI DAN STATUS AKADEMIK ANAK DENGAN KEMANDIRIAN ANAK RETARDASI MENTAL DI SLB YAYASAN PEMBINAAN ANAK CACAT MANADO - Situmeang, Jenny Puspita Sari; Bidjuni, Hendro; Lolong, Jill (Universitas Sam Ratulangi, 2016)
Abstract:Mental retardation is a condition with the characteristics of patients who have the intelligence level(IQ) is below the average, difficult to communicate,care for themselves, making decision, do recreation, working, be healthy and safety. The objective of this study was to know the relationship status of socio-demographic and academic status with the independence of mental retarded children at SLB YPAC Manado. This research using by cross sectional method. Collecting Data using by observation sheet and school report cards of children. The sampling method is purposive sampling. Total of sample is 50 respondents consists of children who have dependent independence and independent. Analysis were processed by chi-square test for probability of 95% (Î±=0,05). The results showed the status of socio-demographic: age (p= 0081), education (p= 0.120), occupation (p= 0.254) and academic status (p= 0.000). Conclusion: there is no relationship between socio-demographic status with the independence of mental retarded children, and there is a relationship between the academic status with the independence of mental retarded children. Suggestion: for health workers, this study can be used as a basic nursing services specifically for psyche nursing care and especially to parents who have children with mental retardation have mild to very severe. Keywords: Socio-Demographic, Academic, Independent mental retarded child Abstrak:Retardasi mental adalah suatu kondisi yang karakteristik penderitanya memiliki tingkat kecerdasan (IQ) dibawah rata-rata, sulit dalam berkomunikasi, mengurus diri sendiri, mengambil keputusan, rekreasi, pekerjaan, kesehatan dan keamanan. Tujuan penelitian ini adalah mengetahui hubungan status sosio demografi dan status akademik dengan kemandirian anak retardasi mental di SLB YPAC Manado. Penelitian ini dilaksanakan dengan metode cross sectional. Data diambil menggunakan lembar observasi/ raport anak retardasi mental. Metode pengambilan sampel adalah Purposive Sampling. Jumlah sampel 50 responden yaitu anak yang memiliki tingkat kemandirian tergantung dan mandiri. selanjutnya data dianalisa menggunakan uji Person chi-square dengan tingkat kemaknaan 95% (Î±=0.05). Hasil penelitian menunjukan status sosio demografi: Usia (p=0.081), Pendidikan (p=0.120), pekerjaan (p=0,254) dan status akademik: (p=0,000). Kesimpulan: tidak terdapat hubungan antara status sosio demografi dengan kemandirian anak retardasi mental, dan terdapat hubungan antara status akademik dengan kemandirian anak retardasi mental. Saran :bagi tenaga kesehatan Penelitian ini dapat digunakan sebagai dasar dalam pemberian pelayanan keperawatan secara khusus pelayanan keperawatan Jiwa, khususnya pada Orang tua yang memiliki anak retardasi mental yang ringan sampai yang sangat berat. Kata Kunci:Sosio Demografi, Akademik, Kemandirian Anak Retardasi Mental